PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERNALAR KRITIS SISWA KELAS V DI SD NEGERI 223 PALEMBANG - Hartini, Putri; Sri Wahyuningsih; Mega Prasrihamni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to improve students' critical reasoning skills in natural and social science (NNS) by using differentiated learning with process differentiation on students' learning styles. This research was conducted at Primary School 223 Palembang in class V. The research method used was quantitative with experimental research type, True Experimental Design with pretest-posttest control group design. This study used a total sampling technique, which amounted to 35 students, from classes V.A and V.B. Data analysis techniques in this study, namely normality test, homogeneity test, and hypothesis testing. From the results of the calculation of hypothesis testing using independent sample t-tests, the Sig. (2-tailed) value is 0.000 <0.05 and the tcount> ttable value is 1.690, which means that based on hypothesis testing H0 is rejected and Ha is accepted. This means that there is an effect of differentiated learning on the critical reasoning ability of grade V students at Primary School 223 Palembang.